Organizational culture and teacher job satisfaction - Lenox, Wanda A., author; Porter, Charles F., advisor; Kennedy, Cathy, committee member; Richburg, Robert W., committee member; Morgan, George A., committee member (Colorado State University. Libraries, 1999)
The purpose of this study was to examine the school organizational culture and the job satisfaction of elementary school teachers in one large urban school district. This study also examined the relationship of school demographic variables and student achievement to school culture and job satisfaction. The school district represented a student population of over 66,000. There were 37,039 students in the elementary schools, 13,749 students in the middle schools, and 15,746 students in the high schools. Data collected with the School Culture Survey (1992) and the Minnesota Satisfaction Questionnaire-short form (1967) were analyzed using descriptive and correlational statistics. School demographic variables (socioeconomic status of school, size of school, and average years of teaching service) and student achievement were also included. The teachers from 22 elementary schools were used to generate the data for this study. The Minnesota Satisfaction Questionnaire-Short Form measured three levels of satisfaction; general/overall job satisfaction, intrinsic job satisfaction, and extrinsic job satisfaction on a 5-point Likert Scale. The School Culture Survey (SCS) total scores were measured on a 5-point Likert Scale in four distinct areas of cultural strength; "strong" culture, "moderately strong" culture, "somewhat weak" culture, and "weak" culture. The schools involved in this study had a mean score of 89.67 ("moderately strong" culture) on the SCS. The strength of the school organizational culture (OC) and teacher job satisfaction were related in the areas of general job satisfaction (r = .59), intrinsic job satisfaction (r = .36), and extrinsic job satisfaction (r = .59). Organizational culture and the size of the school were moderately correlated (r = .65). There was no relationship between the OC, job satisfaction, and student achievement. The average years of teaching service for the district under study was 6-10 years. OC and years of teaching service were not related (r = .1003). Teacher job satisfaction on all three levels was not related to years of teaching service (general job satisfaction, r = .0196, intrinsic job satisfaction, r = .1308, and extrinsic job satisfaction, r = .-0038). The supplemental findings indicated that student achievement was related to socioeconomic status and the size of the school. In addition, it appears that large schools tend to have strong organizational cultures.
Keywords: cultural anthropology; elementary education